2019
DOI: 10.1016/j.devcel.2019.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Forces Regulate Cardiomyocyte Myofilament Maturation via the VCL-SSH1-CFL Axis

Abstract: Highlights d Mechanical forces from cardiac contractility positively regulate VCL in vivo d VCL interacts with actin regulators in cardiomyocytes in response to mechanical forces d VCL facilitates cardiomyocyte myofilament maturation through SSH1 and CFL d Zebrafish cfl1 mutants exhibit cardiomyocyte myofilament disruption

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 98 publications
(138 reference statements)
3
40
0
1
Order By: Relevance
“…Directed hypertrophy determines the overall shape of a chamber while cell division is more evident during ballooning stages in mammalian hearts that undergo rapid increases in size [ 6 ]. Outgrowth occurs as the linear heart has already commenced peristaltic beating and zebrafish studies have shown that blood fluid forces can influence final chamber morphology by affecting cytoskeletal protein localization, cardiomyocyte maturation and also endocardial proliferation [ 7 , 8 , Reviewed 9 ]. Underpinning the directed growth is myofibrillogenesis, the process of assembling the contractile protein machinery within the muscle cells.…”
Section: Introductionmentioning
confidence: 99%
“…Directed hypertrophy determines the overall shape of a chamber while cell division is more evident during ballooning stages in mammalian hearts that undergo rapid increases in size [ 6 ]. Outgrowth occurs as the linear heart has already commenced peristaltic beating and zebrafish studies have shown that blood fluid forces can influence final chamber morphology by affecting cytoskeletal protein localization, cardiomyocyte maturation and also endocardial proliferation [ 7 , 8 , Reviewed 9 ]. Underpinning the directed growth is myofibrillogenesis, the process of assembling the contractile protein machinery within the muscle cells.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it is interesting to note that focal adhesion proteins such as FAK and vinculin also localize to intercalated discs once they form ( Koteliansky and Gneushev, 1983 ; Yi et al , 2003 ). Indeed, a recent study found that vinculin localizes to cell–cell-adhesion sites under increased load in zebrafish hearts in vivo , driving the thickening of myofibrils ( Fukuda et al , 2019 ). Determining the mechanisms driving the localization of such proteins to sites of increased load should be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A proteomic screen in non-contracting and contracting rat cardiomyocytes identified the slingshot protein phosphatase (SSH1) as a vinculin-binding partner in contracting cells (Fukuda et al 2019 ). Indeed, the vinculin-SSH1 interaction was increased by cyclical stretch and abolished when cardiac contractility was inhibited, suggesting that the interaction is force-dependent (Fukuda et al 2019 ). SSH1 can dephosphorylate and activate the actin regulator cofilin (CFL), which severs F-actin filaments to supply monomeric G-actin and promote filament reassembly (Ohashi 2015 ).…”
Section: Mechanosensing and Transduction At The Idmentioning
confidence: 99%
“…Interestingly, neonatal rat cardiomyocytes infected with a phosphomimetic CFL2 adenovirus displayed ‘stress-like’ fibre structures and reduced contractility compared with cells infected with wild-type adenovirus, suggesting that excess actin filament formation is detrimental for contraction (Subramanian et al 2015 ). It may be that CFL recruitment to the vinculin-SSH1 complex is a protective mechanism in response to increased mechanical load since decreased CFL activity is associated with DCM (Fukuda et al 2019 ). It will be interesting to study the precise localisation of CFL in cardiomyocytes, but immunofluorescence microscopy of human hearts revealed that CFL2 is present predominantly at the intercalated disc (Subramanian et al 2015 ), further supporting its role in mechanotransduction at this specialised site.…”
Section: Mechanosensing and Transduction At The Idmentioning
confidence: 99%